PEMBINAAN TAHSIN DAN TAHFIDZ AL-QUR’AN DI TK/TPA NURUL AINI DESA ARALLAE - IIham Ilham; Syarifuddin Syarifuddin; Siar Ni'mah; Asriadi Asriadi; Sulfikar Sulfikar (Fakultas Ushuluddin dan Komunikasi Islam, 2024)
Coaching is defined as an educational effort both formal and non-formal that is carried out consciously, planned, directed, and is responsible for growing, guiding, and developing the basics of personality, knowledge, and skills that are balanced, whole, and harmonious. Talents and abilities possessed as provisions to add, improve and develop themselves, fellow human beings and the environment towards achieving human beings who are dignified, have quality and ability and an independent personality. This activity aims to improve the memorization of short letters and develop knowledge in reading the Qur'an for students, and is expected to play a major role in teaching the ability to read and write the Qur'an as well as strongly support the development of the child's soul as knowledge of worship, faith, and morals considering that the material being taught is not only focused on coaching and tahfidz of the Qur'an but also provides material on tahsinul qira'a (reading improvement). In general, the first step to learning to recite the Koran is to learn to pronounce the hijaiyah letters properly and correctly, or usually known as tahsinul Quran.